Pengaruh Modal Usaha dan Sikap Entrepreneurship terhadap UMK Kuliner Kecamatan Bangkinang Kota Kabupaten Kampar - Linda Sarah; Mariaty Ibrahim (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
This study aims to determine the effect of venture capital and entrepreneurial attitudes on income. The population used in this study was the culinary sector UMK in Bangkinang Kota District, while the sample in this study was 80 culinary UMK. data collection using a questionnaire that has been tested for validity and reliability. The analysis in this study uses descriptive analysis, classical assumption test, multiple linear regression analysis, statistical t test, statistical test f, and test the coefficient of determination. . The results of the f test (0.000), t test of venture capital (5.829) and entrepreneurial attitudes (7.052) and the test of the coefficient of determination (0.823%) from this study indicate that venture capital and entrepreneurial attitudes have a significant effect on income.